Analysis of information literacy skills with data mining techniques - Chanyam, Phanisara; Suwannatthachote, Praweenya; Ngudgratoke, Sungworn (วารสารห้องสมุด สมาคมห้องสมุดแห่งประเทศไทยฯ, 2023)
The objective of this research was to classify the patterns of information literacy skills of Grade 12 students using data mining techniques. The research sample consisted of 384 Grade 12 students in Thailand in the academic year 2021, who had a confidence level of 95%. The data analysis was divided into two steps: The first step was clustering to group the information literacy skills of the students with similar characteristics using the K-means method, which resulted in three clusters based on three indicators: 1) Information sources and information resources, 2) Information retrieval strategies, and 3) Ethical and legal use of the information. The second step was classification to predict the patterns of the information literacy skills of the Grade 12 students obtained from the clustering, which had a total of 74 conditions.